2012
DOI: 10.1557/jmr.2012.234
|View full text |Cite
|
Sign up to set email alerts
|

Highly controlled crystallite size and crystallinity of pure and iron-doped anatase-TiO2nanocrystals by continuous flow supercritical synthesis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
6
33
0
Order By: Relevance
“…The parameter matrix spanned by (i) synthesis temperature, (ii) TTIP concentration in reactant and (iii) water concentration in solvent has previously been shown to affect crystallite size and NP crystallinity in a systematic way. 25 Also, utilizing this particular synthesis allows for very high concentrations of TTIP (>1 M), which yields a dense paste of TiO 2 NPs. For an up-scale laboratory system such as the one presented here, this feature enables "extreme testing" of the production capability and investigation of clogging tendencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter matrix spanned by (i) synthesis temperature, (ii) TTIP concentration in reactant and (iii) water concentration in solvent has previously been shown to affect crystallite size and NP crystallinity in a systematic way. 25 Also, utilizing this particular synthesis allows for very high concentrations of TTIP (>1 M), which yields a dense paste of TiO 2 NPs. For an up-scale laboratory system such as the one presented here, this feature enables "extreme testing" of the production capability and investigation of clogging tendencies.…”
Section: Resultsmentioning
confidence: 99%
“…25 At a concentration of 1.0 M TTIP, the pressure was Table S1. An increase in temperature was found to increase the crystallite size as well as the crystallinity as shown on Figure 5c,d for a TTIP concentration of 0.25 M. In comparison with the earlier study of Mi et al, 25 the overall crystal growth is similar in the respect that high H 2 O contents yield the smallest particles. In this study, remaining trends are less clear than in the previous one which showed clear inverse relationships between crystallite size and water contents.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that TiO 2 films doped with copper [11][12][13], iron [14,15], chromium [16,17], carbon [18,19], nitrogen [20,21] and bismuth [22] improve their properties as photocatalysts in the visible region. However, the antibacterial properties of TiO 2 not only depend on dopants but also other parameters such as crystalline nature, crystalline size, phase composition, chemical composition and synthesis methodology [23].…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Although many salts become increasingly soluble with temperature this behavior changes near the criticalp oint where solubility decreases dramatically.D uring the last decade hydrothermal and solvothermal continuous-flow synthesis became widely used to make al arge range of tailored nanoparticles. [27][28][29][30][31][32] In hydrothermal continuous-flow reactors, the metal salt precursors undergo extremely fast heating upon mixing with as uperheated solvent stream.T his inducesashort nucleation burst,w hich leads to smalln anoparticles with narrows ized isTiO 2 @SnO 2 hybrid nanocomposites were successfully prepared in gram scale using ad ual-stage hydrothermalc ontinuous-flow reactor.T emperature and pH in the secondary reactor were found to selectively direct nucleation and growth of the secondary materiali nto either heterogeneous nanocomposites or separatei ntermixed nanoparticles. At lowp H, 2nmr utile SnO 2 nanoparticles were depositedo n9nm anatase TiO 2 particles; the presence of TiO 2 was found to suppress formation of larger SnO 2 particles.…”
Section: Introductionmentioning
confidence: 99%